Nursing students' experiences during a rural community placement programme in Namibia - 2001 - SN lipinge (AOSIS, 2003)
The reviewed nursing curriculum in Namibia incorporated issues related to Primary Health Care and diversification in the practical field for student nurses. This means that the students are exposed more to their communities than before. Nurses identify, manage and refer, if need be, the problems at this level. The curriculum facilitates and strengthens problem-solving skills and enhances the ability of nurses to adapt a comprehensive and family centred approach.